The Social Novel by Hans Fallada Little Man, What Now? - Zobenica, Nikolina N. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Although the novel by Hans Fallada (born as Rudolf Ditzen, 1893–1947) Little Man, What Now? (Kleiner Mann, was nun?) was published more than eighty years аgо (1932), it was only translated to Serbian in 2015. It can be regarded both as a belated reaction or publication in the right moment – both would be correct. The novel has also regained attention in Germany, and the unabridged edition was published in 2016. Little Man, What Now? is the novel on a little man in the Weimar Republic and depicts the society of that time. In this paper the sociological approach has been applied to the novel analysis in order to show the picture of the society, with the aim to emphasize the timeless features which make this social novel still relevant and interesting. The reference of literature to society is not always obvious as in this case, which serves as the base for criticism of the sociological approach. The assumption that literature has relevance for reality is criticized because it disputes the premise of modern aesthetics that the author is an autonomous creator of art works. Drawing an analogy between literature and society has also been questioned because of numerous difficulties in associating the history of literature to the history of society. In spite of all these critical points, the analysis of this novel has been undertaken from the sociological approach because it directly points at the society in the Weimar Republic. Since it has not lost its actuality decades after its first publication, although it depicts the social circumstances of a certain period of time (1929–1932), it can be concluded that there are social processes which are in a certain way constant despite outward changing circumstances. The consequences of economic instability always strike the „little men“ most severely, not only are they at the mercy of their employers and various institutions, but are also affected by their lack of solidarity as well. The only source of happiness and support can be found in warm human relationships, like friendship, love and family, as Johannes Pinneberg finds them in his life with his Lämmchen.